The Effect of Product Quality and Service Quality on Customer Loyalty through Customer Satisfaction as an Intervening Variable (Study on Vario Motorcycle Users in Sidoarjo) - Yasmin Widyana Damayanti, Nabila; Prabowo, Budi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research was conducted to determine the effect of product quality and service quality on customer loyalty through customer satisfaction for Honda Vario motorbike users in Sidoarjo. The sampling technique used in this research was purposive sampling with a total of 100 respondents. The method used in this research is Partial Least Square (PLS) analysis using SmartPLS 4.0 software. It is known that the results of this research show that 1) product quality has a positive and significant influence on customer satisfaction. 2) Service quality has a positive and significant influence on customer loyalty. 3) product quality does not have a positive and insignificant influence on customer loyalty. 4) Service quality has a positive and significant influence on customer satisfaction. 5) Customer satisfaction has a positive and significant influence on customer loyalty. 6) Product quality has a positive and significant influence through customer satisfaction on customer loyalty. 7) Service quality has a positive and significant influence through customer satisfaction on customer loyalty.